Comparative reproductive biology of pre-, imaginal, and neotenic castes of the Asian termite Coptotermes gestroi (Blattaria, Isoptera, Rhinotermitidae) - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP]; Silva, Iago Bueno da [UNESP] (Cambridge Univ Press, 2022)
The Asian subterranean termite Coptotermes gestroi is a worldwide structural pest, although its reproductive biology has been poorly investigated due to a cryptic habit and occurrence of polycalic nests. In this study, we investigated ovarian development and oogenesis in different-aged females of C. gestroi: fourth-instar nymphs, non-functional neotenics, alates, and functional queens. We show that the ovaries develop gradually according to their age and functionality, as younger individuals possess immature oocytes, whereas alates and functional queens always undergo vitellogenesis. Oocytes were classified into previtellogenic (stages I, II, and III) or vitellogenic (stages IV, V, and VI). Ovary development varied among non-functional neotenics, and a rapid differentiation and/or the presence of primary reproductives are believed to influence such a maturation. Immature oocyte stages were shared between fourth-instar nymphs and neotenics. These characteristics, together with other neotenic features (wing buds, body pigmentation, and eye color), should be evaluated in detail aiming to clarify which nymphal instars differentiate into secondary reproductives. Oogenesis was not uniform among alate females, and cross-sectional area of terminal oocytes was significantly smaller in alates when compared to functional queens, suggesting different degrees of maturation in swarming individuals. Functional queens always had mature terminal oocytes (stage VI). Ovariole number and oocyte maturation in C. gestroi relies on several factors and may therefore differ among individuals of the same caste. Future studies should take into account these reproductive features to evaluate how they impact colony development.
Keywords: Oogenesis; Ovary development; Pest species; Reproduction